Hemifacial Microsomia: A Mini-Review and Case Report - Dehghani Soltani, Anahita; Tehranchi, Azita; Behnia, Hossein; Zahedipour, Fatemeh (Journal of Dental School, 2023)
Objectives Hemifacial microsomia (HFM) is an asymmetric craniofacial malformation, which results from hypoplasia of the first and second branchial arch components and is characterized by a wide spectrum of phenotypic expressions, varying from the underdevelopment of the temporomandibular joint, mandible, facial and trigeminal nerves, masticatory muscles, ears, and hypoplastic maxillary, temporal, orbital, and zygomatic bones to conductive hearing loss due to external and middle ear deformities. Management of this developmental defect is multidisciplinary and associated with various phenotypic spectra and severities. A wide range of treatment protocols, such as surgical interventions, have been proposed, especially for mandibular hypoplasia, including rib or fibular bone grafting, distraction osteogenesis (DO), orthognathic surgery, and a combination of these procedures. Case In this study, the treatment course and 17-year follow-up of a patient with HFM were described. The treatment included autogenous costochondral grafting, followed by full-time application of an asymmetric hybrid functional appliance, fixed orthodontic therapy, orthognathic surgery, and contour modification surgery to achieve optimal facial aesthetics. Conclusion Patients can benefit from functional jaw orthopedics psychosocially and the consequent enhanced facial symmetry during childhood and adolescence is really advantageous